A comparative study of gas explosion occurrences and causes in China and the United States. Issue 4 (3rd July 2016) - Gao, Yan; Fu, Gui; Nieto, Antonio
Abstract : This paper presents a comparative study of gas explosion occurrences and causes in coal mines in China and the US. 170 coal mine accidents related to gas explosions in China are statistically compared to 46 gas explosion accidents in the US by analysing the time, location and ignition source of each accident. Comparative results indicate that in both China and in the US, the peak period for accidents occurred before and after the respective country's holidays. Within a coal mine, the most frequent locations where gas explosion accidents occur are: the coal face, the heading face and the haulage roadway. In China, the gob area is another frequent accident location. Among 15 possible causes for ignition sources resulting in gas explosions, China and the US share 10, and 'Blasting' is the top cause of gas explosion in both countries. In China, the five major causes of gas explosion not present in the US are 'Use of coal electric drill with loss of explosion protection', 'Dismantling the cap lamp', 'Using non-explosion proof electric equipment', 'Spontaneous combustion' and 'Open fire in the gob area'.